Strategi Guru dalam Meningkatkan Motivasi Belajar Siswa di SDIT Al-Manar - Vira Eka Putri; Radhiyatul Fithri; Deprizon Deprizon; Yulia Septi Wahyuni (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Learning motivation is a fundamental pillar of educational success, especially at the elementary level where children’s curiosity and enthusiasm must be nurtured continuously. This study aims to explore the strategies employed by teachers to foster and enhance students’ learning motivation in the IPAS subject at SDIT Al-Manar Pekanbaru. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation. The findings reveal that teachers implemented a variety of strategies not only focused on academic achievement but also attentive to the emotional and individual needs of each student. Contextual learning, cooperative group activities, and the use of rewards and positive reinforcement effectively encouraged students to be more active and confident in their learning. Parental support and a supportive learning environment also played a crucial role in creating an enjoyable and meaningful learning experience. This study highlights that a humanistic and holistic approach by educators not only enhances students’ learning motivation but also fosters meaningful relationships in the educational process.